2016
DOI: 10.1016/bs.apha.2016.01.006
|View full text |Cite
|
Sign up to set email alerts
|

The NMDA Receptor and Schizophrenia

Abstract: Schizophrenia is a severe mental illness that affects almost 1% of the population worldwide. Even though the etiology of schizophrenia is uncertain, it is believed to be a neurodevelopmental disorder that results from a combination of environmental insults and genetic vulnerabilities. Over the past 20 years, there has been a confluence of evidence from many research disciplines pointing to alterations in excitatory signaling, particularly involving hypofunction of the N-methyl-D-aspartate receptor (NMDAR), as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
126
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 242 publications
(130 citation statements)
references
References 156 publications
(195 reference statements)
1
126
0
3
Order By: Relevance
“…Spread throughout the central nervous system (7, 8), NMDARs are integral for fast excitatory signal transmission, essential for normal brain development, and function and are implicated in multiple neurological injuries, diseases and disorders (9). NMDARs play particularly crucial roles in learning and memory and are the targets of clinically relevant drugs for treatment of Alzheimer’s disease (10), schizophrenia (11), depression (12) and epilepsy (13). …”
Section: Introductionmentioning
confidence: 99%
“…Spread throughout the central nervous system (7, 8), NMDARs are integral for fast excitatory signal transmission, essential for normal brain development, and function and are implicated in multiple neurological injuries, diseases and disorders (9). NMDARs play particularly crucial roles in learning and memory and are the targets of clinically relevant drugs for treatment of Alzheimer’s disease (10), schizophrenia (11), depression (12) and epilepsy (13). …”
Section: Introductionmentioning
confidence: 99%
“…10,11 In addition, M 1 functionally interacts with the N -methyl-D-aspartate subtype of the glutamate receptor (NMDAR) 12 and has been shown to reverse behavioral pharmacological (phencyclidine and MK-801) and genetic (NR1 KD mice)NMDAreceptor deficits (i.e., the NMDA receptor hypofunction hypothesis of schizophrenia). 1323 Over the last 30 years, the M 1 muscarinic acetylcholine receptor has emerged as an attractive molecular target for both of these devastating CNS disorders; however, while early efforts with orthosteric muscarinic agonists (activating M 1 –M 5 at varying degrees) showed a trend toward cognitive enhancing efficacy in patients, they failed to meet significant end points for cognition enhancement, a result attributed to dose-limiting nonselective cholinergic agonist adverse effects mediated by the concomitant activation of peripheral M 2 and M 3 receptors. 1325 Similarly, functionally M 1 selective allosteric agonists garnered interest early on.…”
Section: Introductionmentioning
confidence: 99%
“…1323 Over the last 30 years, the M 1 muscarinic acetylcholine receptor has emerged as an attractive molecular target for both of these devastating CNS disorders; however, while early efforts with orthosteric muscarinic agonists (activating M 1 –M 5 at varying degrees) showed a trend toward cognitive enhancing efficacy in patients, they failed to meet significant end points for cognition enhancement, a result attributed to dose-limiting nonselective cholinergic agonist adverse effects mediated by the concomitant activation of peripheral M 2 and M 3 receptors. 1325 Similarly, functionally M 1 selective allosteric agonists garnered interest early on. However, many of these compounds proved to interact with both the orthosteric and allosteric binding sites of the receptor and bound bitopically to the receptor.…”
Section: Introductionmentioning
confidence: 99%
“…13 Previous studies have demonstrated that acute or chronic administration of noncompetitive NMDAR antagonists, including phencyclidine (PCP) and ketamine, induce psychotic-like symptoms and cognitive impairments in animals and healthy individuals and exacerbate symptoms in patients with schizophrenia (see reviews by refs 1,4). Recent copy number variation analysis studies have identified numerous de novo mutations in genes encoding the NMDAR and other proteins within the glutamatergic postsynaptic density associated with increased risk of schizophrenia.…”
Section: Introductionmentioning
confidence: 99%
“…Recent development of several genetic models of reduced NMDAR activity have provided important in vivo systems for studying changes in relevant cortical and limbic circuitry comparable to those observed in schizophrenia (see refs 1,911,13,57,58). While the null mutation of G rin1 , the gene encoding the NR1 subunit of NMDARs, is lethal, a hypomorphic or partial loss-of-function mutation of G rin1 results in an NR1 subunit knockdown (NR1 KD) mouse that is still viable.…”
Section: Introductionmentioning
confidence: 99%